Problem Based Learning Model Assisted by PhET Interactive Simulation Improves Critical Thinking Skills of Elementary School Students - Widiarta, I Gusti Komang Agus Angga Putra; Antara, I Gede Wahyu Suwela; Dewantara, Kadek Andre Karisma (Universitas Pendidikan Ganesha, 2023)
The problems faced by students are difficulties in understanding the questions and not having sufficient ability to work on new questions given by the teacher. The purpose of this study is to analyze the effect of the Problem Based Learning model assisted by the phET application on electricity learning materials. This type of research is quasi-experimental. The research population totaled 192 students. The total number of samples is 35 students. The method for obtaining data is the description test method. The instrument used is a description test. The data analysis technique is descriptive qualitative, quantitative and inferential statistical analysis. The results of the study are the results of the t-test which obtain t-count = 52.07 greater than t-table = 2.034, so that there is a significant difference in critical thinking ability between students who use the conventional model and students who are taught using the Problem-based Learning model assisted by the application of PhET material for class VI elementary school electricity. It was concluded that Problem-based Learning assisted by the PhET application could improve the critical thinking ability of fourth grade elementary school students in electricity material. The implication of this research is that Problem-based Learning can be used to improve critical thinking ability.